A Scoping Review of Gender, Sex and Sexuality Differences in Polysubstance Use in Adolescents and Adults. (12th March 2022) - Goodwin, Shelby R; Moskal, Dezarie; Marks, Russell M; Clark, Ashton E; Squeglia, Lindsay M; Roche, Daniel J O
Abstract: Background: Polysubstance use is a common, problematic behavior that increases risk of harm to self and others. Research suggests that rates may vary based on gender, sex and sexuality. Understanding the current state of this literature may inform prevention and treatment of polysubstance use, leading to reduced public health burden. Objectives: This review aimed to synthesize research on gender, sex and sexuality differences in polysubstance use in adults and adolescents. Methods: A scoping review was conducted using all EBSCO databases, PubMed and Google Scholar to identify articles examining the effects of gender, sex and sexuality on polysubstance use. Polysubstance use was defined broadly as the use of any combination of substances over any time period and included licit (alcohol, tobacco) and illicit substances, concurrent and simultaneous use, from lifetime to daily use and use at any frequency. Studies were considered if they were published in peer-reviewed journals between January 1990 and October 2020 and were written in English. Publicly available data sources were also utilized to fully capture prevalence data that has not been published elsewhere. Results: Findings were mostly inconsistent and often conflicting. Only two findings were generally consistent: adult men were overall more likely to report polysubstance use than adult women, and sexual and gender minorities report more frequent polysubstance use than non-minorities. Conclusions: Research has been unable to clearly elucidate differences in polysubstance use prevalence and patterns according to gender, sex and sexuality. Several recommendations are offered to advance future research and address limitations of current research.